[Rezension von: Hogue, Timothy S., 1990-, The Ten Commandments : monuments of memory, belief, and interpretation] - Monroe, Lauren A. S. (The Biblical archaeology review, 2025)
It can be disorienting to see something familiar in a new light. This is a common experience for students who stumble into courses on the Hebrew Bible and discover texts that often have more to do with the ancient Near East than the Judeo-Christian world in which they typically encounter them. For scholars, such moments […]